Innovations in evidence and proof : integrating theory, research and teaching - Roberts, Paul, 1968-; Redmayne, Mike (Hart, 2007)
Explores and debates the developments in Evidence & Proof scholarship. This book contains essays that cover questions of disciplinary taxonomy, pedagogical method and computer-assisted learning, doctrinal analysis, fact-finding, techniques of adjudication, the ethics of cross-examination, and the implications of behavioural science research.